Materials chemistry: cool conditions for mobile ions. - Hayward, M; Rosseinsky, M (2007)
A complex iron oxide has been made that has an unusual crystal structure suggesting that the oxide ions are surprisingly mobile. This finding could pave the way to other metal-oxide materials with useful properties. ©2007 Nature Publishing Group.